Utilisation of pre-oxidised ore in the pelletised chromite pre-reduction process. (June 2016) - Kleynhans, E.L.J.; Neizel, B.W.; Beukes, J.P.; van Zyl, P.G.
Highlights: Pre-oxidation of chromite ore enhance chromite pre-reduction. Optimum pre-oxidation temperature was 1000 °C for the case study ore. Fe migration from the spinel must be maximised while avoiding Cr2 O3 formation. Improvement of 8.5% in electricity consumption can be achieved during smelting. Also, 14% decrease in the lumpy carbonaceous material requirement can be achieved. Abstract: Ferrochromium is a vital alloy mostly used for the production of stainless steel. It is produced from chromite ore, the only economically exploitable natural chromium resource, through carbothermic smelting in submerged arc or direct current furnaces. The pelletised chromite pre-reduction process is currently the industrially applied ferrochromium production process with the lowest specific electricity consumption. Results obtained from this study proved that the pre-oxidation of chromite ore prior to milling, agglomeration and pre-reduction significantly enhances the level of chromite pre-reduction achieved in the pelletised chromite pre-reduction process. The optimum pre-oxidation temperature was established as the temperature where a balance was achieved between maximising iron (Fe) migration to the surface of ore particles that were pre-oxidised, while avoiding the formation of free eskolaite (Cr2 O3 ). For the case study metallurgical grade chromite ore considered, the optimum pre-oxidation temperature was found to be 1000 °C. Utilising such pre-oxidised ore could theoretically lead to an improvement of approximately 8.5% in the specific electricity consumption and a 14% decrease in the lumpy carbonaceous material required during submerged arc furnace smelting of pelletised chromite pre-reduced feed.